2011
DOI: 10.3109/14653249.2011.602337
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet lysate permits scale-up of dental pulp stromal cells for clinical applications

Abstract: BACKGROUND AIMS. Dental pulp stromal cells (DPSC) are considered to be a promising source of stem cells in the field of regenerative therapy. However, the usage of DPSC in transplantation requires large-scale expansion to cater for the need for clinical quantity without compromising current good manufacturing practice (cGMP). Existing protocols for cell culturing make use of fetal bovine serum (FBS) as a nutritional supplement. Unfortunately, FBS is an undesirable additive to cells because it carries the risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 38 publications
3
54
0
Order By: Relevance
“…The hMSC cultured in media of different compositions resulted in similar morphological variances as previously described for hMSC (38,42,19,20,21). The fastest colony formation and proliferation was observed in the media containing 10% platelet rich plasma.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The hMSC cultured in media of different compositions resulted in similar morphological variances as previously described for hMSC (38,42,19,20,21). The fastest colony formation and proliferation was observed in the media containing 10% platelet rich plasma.…”
Section: Discussionsupporting
confidence: 52%
“…We are fully aware that DPSC were cultivated in a medium containing 2% FCS during first three passages and this may affect the results of the experiment, but on the other hand through this procedure we have been able to clearly define and demonstrate the changes in phenotype, proliferation ability and viability of the tested DPSC. To investigate the differences among the properties of hMSC cultivated in various media supplemented with FCS, or human blood components (49,50,51,52,19,20,21); however neither of them provides statistically relevant results on which we could build.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tavakolinejad et al [36] have also found that treatment with hPRP resulted in a statistically significant increase in cell proliferation of human adipose-derived stem cells. In addition to human adipose-derived stem cells, increased proliferation rate for other types of stem cells with hPRP as the cell culture supplement was confirmed [37][38][39][40]. And the fastest proliferation was observed when hPRP was supplemented in a 10% concentration.…”
Section: Growth Factors or Cytokinesmentioning
confidence: 88%